2014
DOI: 10.1007/s00339-014-8630-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cubic LiNbO3 nanoparticles and their application in vitro bioimaging

Abstract: Stoichiometric LiNbO 3 nanoparticles with regular rhombohedral morphology and high crystallinity were synthesized through a molten salt approach. The assynthesized cubic LiNbO 3 nanoparticles as nanoprobes for long-term imaging in vitro were investigated. The as-synthesized nanoprobes exhibit unique properties of long-term observation without photobleaching, flexibility in excitation wavelength, and excellent photostability. The biocompatibility of LiNbO 3 nanoprobes was determined by in vitro assay of cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…[20][21][22] Recently, LiNbO3 nanoparticles have been used as bio-imaging probes to image cells by taking advantage of the exceptional SHG properties of these particles. [23][24][25] A wider utilization of nanoparticles as SHG bio-imaging probes will require their dimensions to be below 100 nm. 26,27 The NLO properties of nanomaterials can also depend on their size, shape, and/or specific chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Recently, LiNbO3 nanoparticles have been used as bio-imaging probes to image cells by taking advantage of the exceptional SHG properties of these particles. [23][24][25] A wider utilization of nanoparticles as SHG bio-imaging probes will require their dimensions to be below 100 nm. 26,27 The NLO properties of nanomaterials can also depend on their size, shape, and/or specific chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have demonstrated the absence of bleaching, quenching, and blinking in HNPs response [24,25,37] and highlighted the benefits for imaging in terms of signal-tonoise ratio and long-term monitoring of evolving structures [53,54]. Indeed most mechanisms of signal intensity decay and/or variations over time are related to the excitation of resonant electronic states.…”
Section: Photo-stabilitymentioning
confidence: 99%
“…Alternatively, LiNbO 3 can be synthesized by reduction of niobium salts and hydrolysis with LiH [23]. Other authors have proposed a molten salt approach using KNbO 3 as precursor [24]. Note also that colloidal suspensions of KNbO 3 HNPs have been recently commercialized (TiBio Sagl, Comano, Switzerland).…”
Section: Synthesis and Preparation Of Colloidal Suspensionsmentioning
confidence: 99%
“…190 In addition to the popular ZnO and BaTiO 3 NPs, cubic LiNbO 3 NPs and colloidal KTiOPO 4 (KTP) nanocrystals emitted SHG that peaked at 520 nm (with a pulsed laser at 1040 nm) and 512 nm (1024 nm wavelength, 80 MHz repetition rate and 100 fs pulse duration), respectively, which could be used to track mice macrophages. 185 Considering their biocompatibility, the cytotoxicity of five harmonic NPs (KNbO 3 , LiNbO 3 , BaTiO 3 , KTP and Zn) was dose dependent on human adenocarcinoma (A549), adenosquamous carcinoma (HTB-178), lung squamous carcinoma (HTB-182) and non-tumoral BEAS-2B cells. 191 The optical properties of these NPs in harmonic conversion are very similar.…”
Section: Lanthanide-doped Upconverting Nps (Ucnps)mentioning
confidence: 99%